2012
DOI: 10.1002/aoc.2878
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, biological studies and in vitro cytotoxicity on human cancer cell lines of titanium(IV) and tin(IV) derivatives with the α,α′‐dimercapto‐o‐xylene ligand

Abstract: The reaction of α,α′‐dimercapto‐o‐xylene (H2dmox) with different precursors such as SnMe2Cl2, [Ti(η5‐C5H5)2Cl2] and [Ti(η5‐C5H4Me)2Cl2] (1:1) in the presence of two equivalents of NEt3 yielded the complexes [SnMe2(dmox)] (1), [Ti(η5‐C5H5)2(dmox)] (2) and [Ti(η5‐C5H4Me)2(dmox)] (3), respectively. 1–3 have been characterized by spectroscopic methods; in addition, complex 3 has been determined by X‐ray diffraction studies. Furthermore, structural studies based on density functional theory calculations of 1 and 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…This result was expected as compound 21 presents two SnPh3 units which are normally associated with increase of cytotoxic activity due to the interaction of SnPh3 + moieties with protein kinases DNA. The cytotoxic activity of 20 and 21 was lower than that reported for carboxylate tin(IV) complexes (12)(13)(14)(15)(16)(17)(18)(19) [36]. However, a more in depth study of compound 21 against HeLa and Fem-x cell showed the induction of an apoptotic cell death [37].…”
Section: Tin-based Metallodrugsmentioning
confidence: 77%
See 3 more Smart Citations
“…This result was expected as compound 21 presents two SnPh3 units which are normally associated with increase of cytotoxic activity due to the interaction of SnPh3 + moieties with protein kinases DNA. The cytotoxic activity of 20 and 21 was lower than that reported for carboxylate tin(IV) complexes (12)(13)(14)(15)(16)(17)(18)(19) [36]. However, a more in depth study of compound 21 against HeLa and Fem-x cell showed the induction of an apoptotic cell death [37].…”
Section: Tin-based Metallodrugsmentioning
confidence: 77%
“…In addition, the DNA binding studies carried out in simulated body fluid showed the weak interaction of the titanocene compounds with DNA [68]. Our group also synthesized titanocene compounds containing the α,α'-dimercapto-o-xylene as a thiolato ligand (71 and 72, Figure 13) and tested their efficacy against human tumor cell lines HeLa, Fem-x, K562 (Table 4) [36]. When the biological activity was analyzed, an improvement of the cytotoxic activity was observed compared with [Ti(η 5 -C5H5)2Cl2] and [Ti(η 5 -C5H4Me)2Cl2] against the cell lines tested K562, HeLa, and Fem-x with a higher cytotoxicity of 72 and a slight preference against K562 (Table 4) [36].…”
Section: Titanium-based Metallodrugsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various mono‐ and polynuclear organotin(IV) compounds comprised of di‐ or triorganyltin(IV) (organyl = methyl, phenyl, etc.) and carboxylato or thiolato ligands showed high in vitro anticancer activity . Generally, the most active are found to be triphenyltin(IV) compounds (mostly in nM concentration), much more active than cisplatin.…”
Section: Introductionmentioning
confidence: 99%